Recent Advances in Multifunctional Perovskite Materials - Sharma, Poorva; Kumar, Ashwini (IntechOpen, 2022)
This book summarizes current advances in the field of multifunctional perovskite materials, including information on their synthesis, characterization, and properties as well as their use in the fabrication of devices and applications. Chapters address such topics as the physiochemical properties of various perovskite materials, advances in perovskites for solar cells, and multifunctional materials and their numerous applications.